Induction of Tomato Plant Resistance to the Whitefly Bemisia tabaci Using the Entomopathogenic Fungus Beauveria bassiana - Natasya, Resva Lira; Trizelia, Trizelia; Liswarni, Yenny (AGRIUM: Jurnal Ilmu Pertanian, 2026)
Whitefly (Bemisia tabaci) is a major pest on tomato plants. Whiteflies not only attack plants directly but also serve as vectors for viruses that spread diseases such as geminiviruses, causing plants to turn yellow. One alternative for controlling this pest is to use entomopathogenic fungi, such as Beauveria bassiana. This study aimed to isolate a B. bassiana strain that enhances tomato plant resistance to B. tabaci. The experiment was arranged in a Completely Randomized Design (CRD) with six treatments and five replications. The treatments included five isolates of B. bassiana, namely BbWs, TD312, PA221, PD114, and PB21 plus a control. The B. bassiana concentration used was 108 conidia/mL. The fungus was applied by soaking tomato seed lots. Results showed that seed soaking with B. bassiana significantly reduced egg, nymph, and adult populations across all isolates compared to the control. Notably, PA221 and TD312 isolates showed significant nymph suppression. Five weeks after planting, the TD312 isolate resulted in the lowest populations: 20.40 eggs per plant, 7.25 nymphs per plant, and 2.30 adults per plant. Additionally, B. bassiana application affected plant morphology by increasing trichome density; plants treated with TD312 had a trichome density of 616.73 trichomes/cm², higher than the control (295.73 trichomes/cm²). Although statistically comparable to several other isolates on some parameters, TD312 consistently exhibited the lowest pest counts and the highest trichome density, indicating its potential to enhance tomato resistance to B. tabaci by suppressing pest populations and reinforcing trichome density.